2011
DOI: 10.1371/journal.pone.0020273
|View full text |Cite
|
Sign up to set email alerts
|

Subliminal Semantic Priming in Speech

Abstract: Numerous studies have reported subliminal repetition and semantic priming in the visual modality. We transferred this paradigm to the auditory modality. Prime awareness was manipulated by a reduction of sound intensity level. Uncategorized prime words (according to a post-test) were followed by semantically related, unrelated, or repeated target words (presented without intensity reduction) and participants performed a lexical decision task (LDT). Participants with slower reaction times in the LDT showed seman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 55 publications
0
12
1
2
Order By: Relevance
“…But a recent study found semantic priming using auditory prime–target word pairs (Daltrozzo et al, 2011), which was in contrast to the study by Kouider and Dupoux (2005). However, the more recent study showing semantic priming used very low-intensity primes that were not possible to categorize, instead of also using time-compression and masking, which could account for the discrepant findings.…”
Section: From Sounds To Conscious Percepts or Notmentioning
confidence: 60%
“…But a recent study found semantic priming using auditory prime–target word pairs (Daltrozzo et al, 2011), which was in contrast to the study by Kouider and Dupoux (2005). However, the more recent study showing semantic priming used very low-intensity primes that were not possible to categorize, instead of also using time-compression and masking, which could account for the discrepant findings.…”
Section: From Sounds To Conscious Percepts or Notmentioning
confidence: 60%
“…Future approaches could control the level of attention using for instance subliminal stimulation (Daltrozzo et al, 2011). Finding ERP effects of SL under subliminal stimulation would rule out the alternative attentional explanation, indicating that these ERP effects are indices of SL per se and not indirect effects of increased attention to newly learned materials.…”
Section: Exploring Sequential Learning With Event-related Potentialsmentioning
confidence: 99%
“…Like the words, the pseudo‐words were monosyllabic, phonotactically legal and pronounceable, but meaningless combinations of sounds in French. Overall, the pseudo‐words contained all the phonemes of the words, as done in previous studies investigating speech perception (Daltrozzo et al ., ; Signoret et al ., ). The average number of phonemes of the pseudo‐words was carefully matched to that of the words (2.3 for the words against 2.4 for the pseudo‐words; t 718 = −1.52, P > 0.125).…”
Section: Methodsmentioning
confidence: 99%
“…In the auditory modality, recent studies show evidence of lexical processing for stimuli presented below categorization (Kouider & Dupoux, ), and below detection (Signoret et al ., ) thresholds. Semantic processing of auditory stimuli has also been observed below the auditory categorization threshold (Daltrozzo et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation